Nomenclatural notes on Cerasus (Rosaceae) of China: Three earlier isonyms and typification of Prunus glandulosa and P. pseudocerasus - Wang, Hua-Chen; Duan, Yi-Fan; Wang, Xian-Rong (Phytotaxa, 2015)
Three earlier isonyms for three later isonyms of Cerasus of China, C. dolichadenia (Cardot) C. L. Li & S. Y. Jiang, C. glandulosa (Thunberg) Sokolov, and C. pseudocerasus (Lindley) Loudon, are suggested. We also lectotypify Prunus glandulosa Thunberg and discuss the confusing type of P. pseudocerasus Lindley.